Integrating life skills through basketball training program - Suardika, I Kadek; Nakoe, Moh. Rivai; Haryanto, Arief Ibnu; Dadu, Mohammad Son; Datau, Husnina (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Purpose: This research aims to find out how to improve students' life skills through a basketball training program. Method: This research involved 66 basketball extracurricular students in Bone Bolango Regency, who were divided into two groups: experimental group (n = 33) and control group (n = 33). The sampling method used was cluster random sampling. This research was conducted through a quasi-experiment with a pre-test and post-test group design using the Life Skills Scale for Sport (LSSS) scale which consists of eight elements: social skills, leadership, problem solving, decision making, emotional skills, communication, teamwork, and goal setting. Result: This research shows that combining basketball training with a life skills program provides more significant results in improving students' life skills compared to basketball training without a life skills program. The integration of life skills programs in basketball training not only improves students' physical abilities but also life skills that are important for their personal development. Conclusion: The most significant improvements were seen in social skills, indicating that the social aspect of basketball practice is very effective in developing students' interpersonal skills